Del Plan Colombia al Plan Patriota: Impacto del conflicto armado colombiano en el Ecuador, análisis de una estrategia de seguridad subregional - Faivre D’Arcier Flores, Hortense (Revista Complutense de Historia de América, 2006)
The Patriot Plan, a broad military offensive directed against the FARC and financed by the United States, threatens to destabilize the Andean subregion. This is an analysis of the repercussions of its application on the border populations of Ecuador, who are the direct victims, on an ecological and socioeconomic level, of the struggle against the narcoterrorism.
Keywords: Colombia Plan; FARC; Drug trafficking; The United States; Displacements; Ecology